3D‐Printed Titanium Trabecular Scaffolds with Sustained Release of Hypoxia‐Induced Exosomes for Dual‐Mimetic Bone Regeneration - Lincong Luo; Weihan Zheng; Jiaying Li; Tingting Chen; Wanting Xue; Tao Lin; Mingrui Liu; Zi Yan; Jiaxin Yang; Jiamin Li; Jiahao Pu; Yaobin Wu; et al. (Advanced Science)
Abstract Current Ti‐6Al‐4V bone implants lack trabecular structure and pro‑angiogenic cues, both essential for regeneration. Herein, a dual biomimetic strategy is devised that integrates a 3D‐printed biomimetic trabecular porous Ti‐6Al‐4V scaffold (BTPS) with exosome‐loaded PEGDA/GelMA hydrogel microspheres (PGHExo) designed for sustained release. BTPS is designed using Voronoi algorithms and imaging data, and replicates the geometry and mechanical properties of natural bone. Hypoxia‐induced human umbilical vein endothelial cell (HUVEC) derived exosomes (HExo) are encapsulated in PGHExo microspheres via microfluidic technology, enabling controlled release of HExo, and anchored onto BTPS using polydopamine (pDA) modification (BTPS&pDA@PGHExo). BTPS exhibited an elastic modulus of ≈3.2 GPa and a permeability of 11.52 × 10−8 mm2, mimicking natural bone. In vitro assays demonstrated that BTPS&pDA@PGHExo significantly enhanced osteogenesis and angiogenesis. mRNA‐Seq analysis suggested that BTPS&pDA@PGHExo regulates osteogenic and angiogenic gene expression through the activation of pathways including MAPK, mTOR, HIF‐1, and VEGF. In vivo, BTPS&pDA@PGHExo improved bone volume, density, and neovascularization in a rabbit model. This dual biomimetic strategy offers a promising clinical solution, addressing the limitations of conventional Ti‐6Al‐4V scaffolds and providing an innovative approach for personalized bone defect repair.